Caracteres morfoagronômicos e resistência parcial à ferrugem asiática em genótipos precoces de soja - Oliveira, Morony Martins (2017)
Soybean crop, despite the technological evolution, did not reach an average of 4,000 kg ha-1 in Brazil due to the factors of climate, nutrition and soil fertility, genetics and phytosanitary problems. Among them is the rust-soy disease of soybean, caused by the fungus Phakopsora pachyrhizi Syd. & Syd., one of the most severe, with damage ranging up to 100%. Among the management strategies are the use of early genotypes, use of preventive fungicides and cultivars with partial resistance and tolerant to phytopathogen. To obtain resistant cultivars, six dominant genes that condition vertical (qualitative) resistance, have already been reported in the literature, but the stability of this type of resistance is not durable. Therefore, the identification of genotypes that can be used as sources of horizontal (quantitative) resistance is essential to increase the longevity of the cultivars launched in the Brazilian market. This work aimed to evaluate the resistance of 12 soybean genotypes to the pathogen and yield responses. This work was developed at Fazenda do Glória, in Federal University of Uberlândia (UFU), located in the city of Uberlândia, MG, Brazil. In the agricultural year 2015/2016 an experiment was carried out with subplots with or without fungicide AZOXISTROBINA + BENZOVINDIFLUPIR and subsubplots related to the evaluation position in the plant. There were 12 early-cycle genotypes, 10 from the UFU germplasm laboratory (LAGER), a commercial susceptible control, and a known resistant LAGER control. They were outlined in randomized blocks with four replicates. The experimental plots were represented by two rows of 6 m x 0.5 m, and the 2.5 m 2 area consisted of the two central rows, eliminating 0.5 m at each end of the plot. The LAGER-210 and LAGER-216 genotypes were selected for crop and use value (CUV) studies because they showed partial resistance to rust, tolerance, short cycle, good morphoagronomic characteristics and higher yields.